Principles of information systems : a managerial approach - Stair, Ralph M.; Reynolds, George W. (Australia : Thomson Learning Asia, 2001)
Offers teh traditional coverage of computer concepts, but it palces the material within teh context of business and information systems.
Part I: Overview -- Part II: Information technology concepts -- Part III: Business information systems -- Part IV: Systems development -- Part V: Information systems in business and society
Includes index.
Keywords: MANAGEMENT INFORMATION SYSTEMS